Answer:
C
Step-by-step explanation:
The formula for any geometric sequence is:
[tex]a_n=a_1\cdot r^{n-1}[/tex]
Where aₙ is the value of the nth term, a₁ is the value of the first term, r represents the common ratio, and n represents the term number.
We want the formula for the geometric sequence:
-3, -6, -12, -24, ...
Note that our first term is -3. Hence, a₁ = -3.
Next, each subsequent term is twice the previous term. Hence, our common ratio r = 2.
Therefore, by substitution, we acquire:
[tex]a_n=-3\cdot (2)^{n-1}[/tex]
Our answer is C.